De la forma a la estructura en tecnología lítica: una nueva metodología para los Andes Centrales (Perú) - Pérez-Balarezo, Antonio; Tarrillo, Dany; Vergara, Daniel; Córdova, Renzo; Becerra, Christian; Battistini, Aixa; Brescia, Brunella; Gutiérrez, Paolo; Esquivel, Fabiana; González-Varas, Marina; Silva, Edwin (Pontificia Universidad Católica del Perú, 2025)
This article presents a methodology for the technostructural analysis of carved lithic artifacts that aims to understand how tools were used in the past. The proposal is based on the premise that all tools are a threefold structured system that comprises three parts: transformative, prehensility and energy reception. An artifact belonging to the lithic assemblage recovered at the site of Vadopampa in Ayacucho, Peru, has been analysed with the help of students as an example of the application of the technostructural approach. The paper thus introduces a new methodology for the Central Andes in a didactic and critical way, promotes a dynamic perspective for lithic tools, and assesses the potential and the limits of all technological interpretations.

Este artículo presenta una metodología de análisis tecnoestructural de artefactos líticos tallados cuyo objetivo es comprender cómo funcionaron en el pasado. Esta propuesta se basa en la premisa de que todo instrumento es un sistema estructurado compuesto por tres partes: transformativa, prensil y receptiva de la energía. Con la participación de estudiantes de diferentes niveles universitarios, se analiza un artefacto del conjunto lítico recuperado en el sitio de Vadopampa, Ayacucho, Perú, como ejemplo de aplicación de un análisis tecnoestructural. En este sentido, este trabajo busca introducir una nueva metodología para los Andes Centrales de manera didáctica y crítica, promoviendo una perspectiva dinámica del instrumental lítico y evaluando los potenciales y límites de cualquier interpretación tecnológica.
Form to structure in lithic technology: a new methodology for the central Andes (Peru)
Keywords: Lithic technology; Ayacucho; Peru; Structure; Ergonomics; Tecnología lítica; Ayacucho; Perú; Estructura; Funcionamiento; https://purl.org/pe-repo/ocde/ford#6.01.02